Computational Chemical Interactions Study and Characterization of Rutin-Malic Acid and Rutin-Nicotinamide Binary Mixture by Microwave Irradiation - Winantari, Agnes Nuniek; Dewantara, Djayawati Poetri; Sumartha, I Gede Ari; Rani, Karina Citra; Pradana, Aditya Trias; Kesuma, Dini (Science and Technology Indonesia, 2026)
Rutin is a saf flavonol glycoside with potent antioxidant activities. However, its low water solubility (122.6–126 μg/mL) limits rutin applications. Binary mixtures of rutin–malic acid (R-MA) and rutin–nicotinamide (R-NIC) are among the strategies used to improve rutin’s solubility. This research aimed to evaluate the chemical interactions and physical characteristics of both binary mixtures (in equimolar ratios). The chemical interactions of R-MA and R-NIC were studied using the molecular docking method (AutoDock4). The results showed that the lowest binding energies of R-MA and R-NIC were −1.18 kcal/mol and −2.77 kcal/mol, respectively, with evidence of hydrogen bonding and π–π stacking interactions. The binary mixtures of R-MA (1:1) and R-NIC (1:1) were prepared by the microwave irradiation method. R-MA (1:1) and R-NIC (1:1) were prepared by slurrying under continuous stirring at 120 rpm, 70 °C for 4 min, and the microwave irradiation energy was set to 300 Watt for 5 min of exposure time. The formed binary mixture physical characteristics were evaluated using PXRD, DSC, FTIR, and SEM. The characterization results indicated the presence of a binary mixture. Compared to the physical mixture and their parent components (rutin, MA/NIC), diffractograms, thermograms, and IR spectrums respectively showed that the binary mixture has similar crystallinity profiles, decreased endothermic peaks, and not significantly shifted wavenumbers. Morphology analysis depicted that rutin, MA, and NIC are acicular, plate, and columnar shaped, respectively, while both binary mixtures showed an agglomerated fine needle-like, irregular shape, and rough-surface particles. This research shows that the binary mixtures of R-MA and R-NIC were successfully formed using this method, in accordance with chemical interaction predictions.